Methyl coenzyme M reductase as a target for inhibition of methanogenesis in ruminants: challenges and opportunities - Shao, Zhiyong; Lu, Zheng; Wu, Lijun; Liu, Wei; Abdullah, Muhammad; Hassan, Faiz-ul; Chen, Xiabing; Cao, Ruige; He, Bin (Frontiers in Microbiology, 2026)
Enteric methane from ruminants is a major source of greenhouse gasses (GHG) emissions globally, and its formation also leads to a decrease in animals’ productivity due to loss of dietary energy. Reducing enteric methane emissions is essential for mitigating greenhouse gas–driven climate changes while simultaneously enhancing ruminant production efficiency. Methanogens residing in the rumen are responsible for enteric methane production. They reduce carbon dioxide to methane with the help of hydrogen, thus playing a crucial role in global methane emissions. Methyl coenzyme M reductase (MCR) is a key enzyme in methanogens that catalyzes the final step of methanogenesis. This review consolidates information on MCR enzyme’s structure, cofactor chemistry, and post-translational modifications (PTMs), followed by a critical appraisal of inhibition strategies using synthetic compounds like 3-nitrooxypropanol (3-NOP) and bromoethanesulfonate (BES) along with their mode of action. Modern in silico studies for the identification of novel natural MCR inhibitors have also been discussed. Blocking MCR through synthetic or natural compounds is a promising approach for mitigating methane emissions from ruminants, allowing the rest of the rumen’s microbial community to function normally. By specifically blocking MCR, hydrogen and other byproducts of carbohydrate fermentation are still consumed, allowing the animal’s digestion and productivity to remain unaffected while significantly reducing its contribution to greenhouse gas emissions. Making it a target, the issue of methane emission in ruminants can be solved without affecting the overall rumen microbiota. Moreover, challenges (hydrogen accumulation, cost, and regulatory hurdles) and emerging opportunities regarding MCR inhibitory strategies are proposed to guide targeted research for scalable methane mitigation in ruminants.